Masyarakat Ekonomi ASEAN (MEA): Persepsi Kompetensi Lulusan Akuntansi di Jakarta - Prabowo, Ananto; Ameliyah, Lia (IAIN Kudus, 2020)
This study aims to determine the perceptions between accounting students, accountant educators, and public accountants at universities and Public Accounting Firms at South Jakarta relate to competencies accounting graduate compulsory requirements in the era of the ASEAN Economic Community. Competency attributes utilized are based on International Education Standards (IES) issued by the International Federation of Accountants (IFAC). The data is the primary data obtained from the distribution of questionnaires. The methods of analysis used independent sample t-test and ANOVA. The results of this research suggest a difference in perception between accounting student, accountant educator, and public accountant toward competence required by accounting graduates in the era of the ASEAN Economic Community (AEC). Business strategy and management, interpersonal and communication skills, and audit and assurance are important competencies of each group of respondents.